Dardanus sanguinocarpus Degener, 1925 (Crustacea: Decapoda: Anomura: Diogenidae) species complex: a redescription of D. sanguinocarpus and descriptions of three new species - Asakura, Akira (Zootaxa, 2006)
Examination of Dardanus sanguinocarpus Degener, 1925 (type locality Hawaii), and specimens closely allied to D. sanguinocarpus collected from several localities in the western Pacific revealed the existence of three hitherto unknown species superficially resembling D. sanguinocarpus. These three species are described here as D. robustus, sp. nov., D. longior, sp. nov., and D. umbella, sp. nov., and Dardanus sanguinocarpus is redescribed.